Design and Implementation Tunable Band Pass Filter based on PCF-Air Micro-cavity FBG Fabry-Perot Resonator - Mohammed, Faraqid Q.; Mansour, Tahreer S. (Iraqi Journal of Laser, 2019)
A tunable band pass filter based on fiber Bragg grating sensor using an in-fiber Mach-Zender interferometer with dual micro-cavities is presented. The micro-cavity was formed by splicing together a conventional single-mode fiber and a solid core photonic crystal fiber (SCPCF) with simple arc discharge technique. Different parameters such as arc power, length of the SCPCF and the overlap gap between samples were considered to control the fabrication process. The ellipsoidal air-cavity between the two fibers forms Fabry-Perot cavity. The diffraction loss was very low due to short cavity length. Ellipsoidal shape micro-cavities were experimentally achieved parallel to the propagation axis having dimensions of (24.92 – 62.32) μm of width and (3.82 – 18.2) μm of length. The maximum tunability 0.73nm was achieved at minimum length of (SCPCF) in the range (1545.673-1545.546) nm. A micro- cavity with width and length as high as 62.32 um and 18.3 um have higher sensitivity 0.31 nm/cm than temperature sensitivities of 18 pm/°C.